1999
DOI: 10.5694/j.1326-5377.1999.tb127904.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A outbreaks among illicit drug users and their contacts in Queensland, 1997

Abstract: Objective To describe five outbreaks of hepatitis A virus (HAV) infection associated with illicit drug use during a statewide outbreak of HAV infection in Queensland. Design Risk factor prevalence survey. Patients and setting All 875 cases of HAV infection notified to Public Health Units in Queensland in the 12 months to 30 November 1997. Main outcome measure Type and prevalence of illicit drug use. Results Risk factor assessment was completed for 804 cases (91.9%). We identified five outbreaks of HAV infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…Outbreaks among IDUs have been reported more often in low endemic areas, compared to highly endemic areas [4][5][6][7][8][9][10][11][12][13], yet it is not known whether the differences are a result of the efficiency of surveillance systems. It is possible that in highly endemic countries infection occurs early in life and that a low proportion of the population thus remains susceptible in young adulthood, when injecting drug use usually begins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Outbreaks among IDUs have been reported more often in low endemic areas, compared to highly endemic areas [4][5][6][7][8][9][10][11][12][13], yet it is not known whether the differences are a result of the efficiency of surveillance systems. It is possible that in highly endemic countries infection occurs early in life and that a low proportion of the population thus remains susceptible in young adulthood, when injecting drug use usually begins.…”
Section: Discussionmentioning
confidence: 99%
“…In non-endemic countries, both large and small outbreaks of HAV infection among IDUs have occurred [4][5][6][7][8][9][10][11][12][13]. In some outbreaks, the prevalent variant was genotype IA [4,5] or IIIA [7,11]; co-circulation of different strains was also reported [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Parenteral spread can also occur in injecting drug users, haemophiliacs using contaminated factor VIII, and other recipients of blood products. [7][8][9][10][11] Sexual transmission There are now numerous reports of HAV outbreaks among men who have sex with men (MSM). Infection correlates with visits to saunas and darkrooms, sex with anonymous partners, group sex, oro-anal and digital-rectal intercourse, and number of partners.…”
Section: Hepatitis a Epidemiologymentioning
confidence: 99%
“…Serological human leukocyte antigen (HLA) A and B typing was performed by An epidemic of reactive arthritis in Vanuatu: a descriptive study 1 Cases of hepatitis A among illicit drug users have been reported previously in southeast Sydney.? Despite the reports of hepatitis A outbreaks among illicit drug users nationally'< and internationally," the route of transmission in most cases remains unclear and is probably multifactorial.…”
Section: Keith Woollardmentioning
confidence: 99%